2017
DOI: 10.1016/j.soard.2016.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Blunting of adaptive thermogenesis as a potential additional mechanism to promote weight loss after gastric bypass

Abstract: BACKGROUND Adaptive thermogenesis (AT) is described as a change in resting metabolic rate (RMR) that is greater than would be predicted from changes in lean body mass (LBM) and fat mass (FM) alone during periods of energy imbalance. Whereas an AT-related downregulation of RMR has been implicated in suboptimal weight loss and weight regain following non-surgical weight loss, defense against AT may underpin the durable weight loss following laparoscopic Roux-en-Y gastric bypass (LRYGB) and other bariatric surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 22 publications
1
17
0
1
Order By: Relevance
“…However, RYGB is associated with “paradoxical” increases in weight‐adjusted resting energy expenditure despite large WL . Blunted adaptive thermogenesis (the difference between measured and expected resting energy expenditure) may also help maintain weight stability after RYGB . Consistent with this, another study showed that subjects who maintained WL had larger diet‐induced thermogenesis than subjects who regained weight after RYGB .…”
Section: Discussionmentioning
confidence: 87%
“…However, RYGB is associated with “paradoxical” increases in weight‐adjusted resting energy expenditure despite large WL . Blunted adaptive thermogenesis (the difference between measured and expected resting energy expenditure) may also help maintain weight stability after RYGB . Consistent with this, another study showed that subjects who maintained WL had larger diet‐induced thermogenesis than subjects who regained weight after RYGB .…”
Section: Discussionmentioning
confidence: 87%
“…6 Recent reports further suggest that adaptive thermogenesis and resting metabolic rates are both blunted after gastric bypass. 7 In this context, our contrarian observations of altered uridine postmeal excursions that persist despite weight loss warrant further investigation. We propose that there may potentially be an important mechanistic role for uridine in the persistent impaired thermoregulation observed in subjects with obesity, even after surgically induced weight loss.…”
mentioning
confidence: 86%
“…AT was only presented for the 20 % fat/15 %PRO and 20 %fat/25 %PRO groups, while the other two groups (40 % fat/15 %PRO and 40 % fat/25 % PRO) did not report AT despite significant WL. Despite the evidence for AT when measured immediately after the WL intervention, some intervention studies reported that this (48) de Jonge et al (29) Karl et al (24) 10-15 % Doucet et al (32) Men Women Byrne et al (20) Redman et al (52) CR and LCD Exercise CR Lecoultre et al (51) CR and LCD Diet and Exercise CR NRT < 5 % Hopkins et al (40) Bosy Westphal et al (31) 5 a 10 % Müller et al (22) Camps et al (27) Goele et al (30) Camps et al (25) 10-20 % Bosy-Westphal et al (28) Weight regainers Thom et al (17) Nymo et al (18) > 20 % Gomez-Arbelaez et al (19) Rosenbaum et al (21) Dulloo et al (33) RT < 10 % McNeil et al (23) Observational < 10 % Ten Haaf et al (47) 10-20 % Pourhassan et al (26) Marlatt et al (50) Martins et al (16) Coupaye et al (39) 20-30 % Wolfe et al (34) Tam et al (37) Browning et al (36) Ravelli et al (53) > 30 % Bettini et al (35) Carrasco et al (38) Johannsen et al (13) Fothergill et al (12) WL, weight loss; WM, weight maintenance; CR, caloric restriction; LCD, low-calorie diet; reported a higher-than-expected decrease for REE/TDEE/SEE (AT), did not report AT. disappeared or was attenuated after a period of weight stabilisation (measured after the follow-up period) (24,27,29) .…”
Section: Diet-only Interventionsmentioning
confidence: 99%
“…Bariatric surgery. For bariatric surgery, six studies were included in this review (34)(35)(36)(37)(38)(39) , with the study length ranging from 6 to 24 months.…”
Section: Diet-only Interventionsmentioning
confidence: 99%
See 1 more Smart Citation